2020
DOI: 10.1111/lasr.12470
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Second-Order Legal Consciousness: Authorities’ Perceptions of “Street Policy” and Welfare Fraud Enforcement

Abstract: Legal authorities’ second‐order legal consciousness—their perceptions of others’ understandings of law—shapes the social realization of legal power. Analysis of interviews with welfare fraud enforcement workers from five US states reveals their perceptions of how clients view law, policy, and enforcement practices, and shows these perceptions’ consequences. Enforcement workers’ perceptions influence the discretionary work of policy implementation, as fraud workers attempt to circumvent what they see as clients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 61 publications
4
20
0
Order By: Relevance
“…Parole candidates are scrutinized for signs that their remorse is genuine, versus following a script. This finding echoes Headworth's description of welfare fraud enforcers, who expressed frustration that welfare recipients shared advice with each other about what to say or how to act to ensure that they would receive food stamps (Headworth, 2020, p. 332). Headworth found that the enforcers he studied do not want to reward people who “game” the system or do not truly “buy into it.” So, too, parole commissioners sought signs that a parole candidate was not so rehearsed that his remorse appeared artificial.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Parole candidates are scrutinized for signs that their remorse is genuine, versus following a script. This finding echoes Headworth's description of welfare fraud enforcers, who expressed frustration that welfare recipients shared advice with each other about what to say or how to act to ensure that they would receive food stamps (Headworth, 2020, p. 332). Headworth found that the enforcers he studied do not want to reward people who “game” the system or do not truly “buy into it.” So, too, parole commissioners sought signs that a parole candidate was not so rehearsed that his remorse appeared artificial.…”
Section: Discussionmentioning
confidence: 59%
“…Previous work on relational and second‐order legal consciousness has spanned a variety of substantive settings. Young (2014) and Headworth (2020) each examined opposite sides of the enforcement coin, looking at how the legal consciousness of enforcer/subject is influenced by each group's beliefs about the other group's legal consciousness. Abrego (2019) and Wang (2019) show the manifold relational ways that legal consciousness (specifically, understandings of citizenship in Abrego's analysis; disputes over eldercare and inheritance in Wang's) are produced and shaped within families.…”
Section: Legal Consciousness and Emotionmentioning
confidence: 99%
See 1 more Smart Citation
“…Language errors could also signal lower educational attainment, and perhaps lower social class. Given the general stigma against less educated and poorer people-and fraud workers' common distrust of poor people who participate in welfare programs (Headworth, 2020)-such signals could similarly make LEP reporters seem less reliable and their reports therefore less promising, discouraging bureaucratic gatekeepers from investing time and energy in them. Hence:…”
Section: Race Ethnicity Immigration and Welfare Workers' Decision-makingmentioning
confidence: 99%
“… 3 For more details on welfare fraud investigation policies and practices, see Headworth (2019, 2020); Headworth and Ossei-Owusu (2017).…”
mentioning
confidence: 99%